HUBUNGAN RIWAYAT PENYAKIT ISPA DAN DIARE DENGAN STATUS GIZI PADA ANAK USIA 1 – 5 TAHUN - Ratna Indriati; Sri Aminingsih (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2020)
Background. Malnutrition in children can affect growth and development. Infectious diseases are also associated with malnutrition, including diarrhea and Acute Respiratory Infections where this condition still occurs in Posyandu Kusuma, Palur Village.The Aim of the Study. To find the relationship between the history of acute respiratory infections and diarrhea with the nutritional status of children. Subject and Method. Subject were 47 of children 1-5 years old in Posyandu Kusuma at Palur Village. This research was observational analytic and correlation design with cross sectional method. Sampling by accidental sampling. The data obtained were analyzed using the Chi Square test.Result. The children with a history of diarrhea wereÂ 8 (17%), 39 with no history of diarrhea (83%), 16 with history of acute respiratory infections (34%), 31 with no history of acute respiratory infections (66%). The Childrens with good nutritional status were 34 (72.3%), 13 underweight nutritional status (27.7%). The results showed that the relationship of diarrhea history obtained p = 0.001 and a history of Acute Respiratory Infections obtained p = 0.693 to nutritional status.Conclusion. History of diarrhea has a significant relationship with the nutritional status of children (p=0.001) and a history of acute respiratory infections has no relationship with the nutritional status of children (p=0.693).Keywords : diarrhea, history of acute respiratory infections, nutritional status.Korespondensi: Ratna Indriati. AKPER PANTI KOSALA SURAKARTA. Jalan Raya Solo-Baki Km. 4 Gedangan, Grogol, Sukoharjo, Jawa Tengah. Email: ratna24173@gmail.com.Â